Impact of environmental, social, governance, and corporate social responsibility factors on firm's marketing expenses and firm value: A panel study of US companies - Nermain Al-Issa; Audil Rashid Khaki; Ammar Jreisat; Somar Al-Mohamad; Dina Fahl; Emira Limani (Cogent Business & Management, 2022)
During recent times of uncertainty, sustainable marketing and sustainable finance became hot research topics attracting both academics and practitioners. Although centering marketing efforts around the firm's Environmental, Social, and Governance (ESG) and Corporate Social Responsibility (CSR) policies allow for creating a superior image and increasing brand value, the incorporation of ESG/CSR activities might seem to be costly and have been claimed to not provide direct marketing benefits. This study aims to explore the impact of firms' ESG/CSR engagement on marketing expenses and firms' market value to provide a strategic rationale for firms to undertake ESG/CSR activities to position their companies distinctly in the marketplace accordingly. The study employs a panel regression to analyze the impact of ESG and CSR commitments on a firm's marketing expenses in a sample of S&P 500 firms in the United States. The results indicate that the firms with higher CSR engagement spend proportionately lesser on their marketing expenses and entertain a higher market value. The results also suggest that the firm's board size, board diversity, and social engagement considerably enhance the firm's market value. The results indicate that focusing on firms' environmental responsibility alone does not sufficiently contribute to enhancing the value of the firm, stakeholders are rather more concerned about the firm's societal engagement which must, therefore, be overtly communicated and reported.
Keywords: 650; sustainable finance; sustainability; CSR disclosure; ESG engagement; marketing performance; stakeholder Theory; sustainable marketing